Antioxidant Activities and Protective Effects of Dendropachol, a New Bisbibenzyl Compound from Dendrobium pachyglossum, on Hydrogen Peroxide-Induced Oxidative Stress in HaCaT Keratinocytes - Sakan Warinhomhoun; Chawanphat Muangnoi; Visarut Buranasudja; Wanwimon Mekboonsonglarp; Pornchai Rojsitthisak; Kittisak Likhitwitayawuid; Boonchoo Sritularak (MDPI AG, 2021)
Five compounds including a new bisbibenzyl named dendropachol (1) and four known compounds (2-5) comprising 4,5-dihydroxy-2,3-dimethoxy-9,10-dihydrophenanthrene (2), gigantol (3), moscatilin (4) and 4,5,4'-trihydroxy-3,3'-dimethoxybibenzyl (5) were isolated from a methanolic extract of Dendrobium pachyglossum (Orchidaceae). The chemical structures of the isolated compounds were characterized by spectroscopic methods. Dendropachol (1) was investigated for its protective effects on hydrogen peroxide (H2O2)-induced oxidative stress in HaCaT keratinocytes. Compound 1 showed strong free radical scavenging compared to the positive control. For the cytoprotective effect, compound 1 increased the activities of GPx and CAT and the level of GSH but reduced intracellular reactive oxygen species (ROS) generation and accumulation. In addition, compound 1 significantly diminished the expression of p53, Bax, and cytochrome C proteins, decreased the activities of caspase-3 and caspase-9, and increased Bcl-2 protein. The results suggested that compound 1 exhibited antioxidant activities and protective effects in keratinocytes against oxidative stress induced by H2O2.